(untitled) (Journal of University of Babylon for Engineering Sciences, 2019)
The variation between flow depth generated in front of gabion barrier and flow rate has been studied in open laboratory flume. Flow profiles have been observed for each of "Transition Flow" and "Overflow" regimes. Effects of gabion height and material coarseness on the upstream flow depth are studied by testing four different gabion heights and four different medium aggregate sizes. The analysis of experimental results showed that the relative decrease in flow depth varies between 38% and 17% for "Through Flow" type when material coarseness and discharge increase. In "Transition Flow" regime, increasing material coarseness and discharge causes an average decreases in relative flow depth of 7.6% and 4.4% for gabion heights 15cm and 30cm, respectively. Gabion begins to operate as an overflow weir when the average water depth to the gabion height (H/P) is 1.19. While the overall average increase in discharge relative to solid weir is 15%. Prediction relationships for flow depth upstream the gabion for each of the three flow regimes is suggested. Also, dimensionless relation to predict discharge coefficient are proposed with good accuracy.